Advantages of Literature (2):: Point of View and Communicative Benefits for Careers and Living a Life - Ruangkhian, Chiratat; Deekawong, Korawan (Academic and Research Journal of Liberal Arts (Online), 2021)
The benefits derived from the understanding of the point of view can be divided into two parts: benefits for speakers (narrators) and benefits for listeners (audience). (1) For speakers, in narrating a story, they should be aware of the reliability of the information. Making reliable information needs objectivity, accuracy, valid source, being recent and verifiable. Besides, all speakers need to have decency and characters. (2) Regarding listening, listeners rely on their wisdom and knowledge in receiving information. Before making a decision, believing or trusting in any information, they need to search for all possible types of evidence and things related to the story and its narrator to prove whether the information is correct and reliable. If the speakers and listeners fathom the literary device, point of view, they can apply it to daily communication creatively and effectively.